(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the theoretical and methodological foundations of patriotic education among young people. It reveals the role of philosophical, social and spiritual factors in shaping attitudes toward patriotism in society. It also highlights issues of strengthening patriotic education within the framework of the national development strategy. Formation and education of a sense of patriotism in the spiritual education of the younger generation is one of the important scientific and practical directions in the field of modern philosophy, social psychology and pedagogy. Devotion to the Motherland, a sense of love for the country not only form the character of an individual, but also play an important role in ensuring stability in society. To analyze the theoretical and methodological foundations of this process, understand its content and develop practical recommendations, it is necessary to pay attention to the following aspects: philosophical approach, socio-philosophical point of view, pedagogical theories, structural-systemic approach, comparative analysis, interactive methods and scientific-theoretical provisions.